The Relevance of Adiponectin and Resistin Levels with Oxidative Stress in Insulin Resistant Type 2 Diabetes - Fares Hassen Hassani (Kufa Journal for Nursing Sciences)
Objectives: The present study was designed to verify the changes of adiponectin and resistin with oxidative stress in insulin resistant in diabetes mellitus type 2.